Enteropathogens and risk factors for diarrhea in Norwegian dairy calves - Gulliksen, S.M. (J Dairy Sci, 2009)
The aims of the current study were to estimate the prevalence of enteropathogens in calves in Norwegian dairy herds, evaluate the clinical consequences of protozoal infections, and identify risk factors for diarrhea. The 135 participating herds were randomly selected from those in The Norwegian Dairy Herd Recording System that had at least 15 cow-years. Each herd was followed for 1 yr. Fecal samples from calves with (n = 68) or without (n = 691) diarrhea were analyzed for the presence of Cryptosporidium, Giardia, and Eimeria species. Diarrheic samples (n = 191) were assayed for rotavirus group A, bovine coronavirus (BCoV), Cryptosporidium, and Escherichia coli F5 by antigen ELISA. Blood samples (n = 1,348) were analyzed for antibodies against BCoV and rotavirus. Potential risk factors for diarrhea were analyzed by using Cox regression analysis adjusted for herd frailty effect. Rotavirus and Cryptosporidium were the most commonly detected enteropathogens in diarrheic samples. A high level of Cryptosporidium shedding or BCoV seropositive calves in a herd was associated with an increased risk of diarrhea. Other factors found to increase the risk of diarrhea were use of slatted concrete floor in group pens versus other floor types [hazard ratio (HR) = 8.9], housing of calves in free-stalls compared with tie-stalls (HR = 3.7), purchasing of calves into the herd versus not purchasing calves (HR = 4.1), and calves being born during winter compared with other seasons of the year (HR = 1.5).